Using Intelligent Tutoring Systems Through Cognitive Tutor Authoring Tools to Solve Filling Slot Problems - Hermawan, Faried (Universitas Islam Negeri Sunan Kudus, 2022)
Intelligent Tutoring Systems (ITS) is a computer system that provides instructions and is adapted to students who apply learning by doing theory. Cognitive Tutor Authoring Tools (CTAT) is one of ITS that supports the creation of flexible tutors for simple problems and complex solutions, able to support several strategies so that they can describe what students do when solving problems. In working on the problem of filling the place, students will solve the problem according to the students' logic of thinking. This is because the logic of thinking of each student is different depending on the information he receives. For this reason, in this study, the use of CTAT will be tried in working on filling slot questions using media, namely Intelligent Tutoring Systems (ITS) which uses Cognitive Tutor Authoring Tools (CTAT) tools. In this study, students have obtained the filling slot material first. Only then is the media used which will later be used to work on filling slot questions with different problems. From this research, it was found that the results of the study were increasing students' understanding in working on filling slot questions using Cognitive Tutor Authoring Tools (CTAT) media.So that the Cognitive Tutor Authoring Tools (CTAT) media can be used as an alternative learning media to develop students' understanding of filling slot material.Intelligent Tutoring Systems (ITS) adalah sistem komputer yang memberikan instruksi dan disesuaikan dengan siswa yang menerapkan learning by doing theory. Cognitive Tutor Authoring Tools (CTAT) merupakan salah satu ITS yang mendukung terciptanya tutor yang fleksibel untuk masalah sederhana dan solusi kompleks, mampu mendukung beberapa strategi sehingga dapat menggambarkan apa yang dilakukan siswa saat menyelesaikan masalah. Dalam mengerjakan soal aturan pengisian tempat, siswa akan menyelesaikan soal tersebut sesuai dengan logika berpikir siswa. Hal ini dikarenakan logika berpikir setiap siswa berbeda-beda tergantung dari informasi yang diterimanya. Untuk itu pada penelitian ini akan dicoba penggunaan CTAT dalam mengerjakan soal aturan pengisian tempat menggunakan media yaitu Intelligent Tutoring Systems (ITS) yang menggunakan tools Cognitive Tutor Authoring Tools (CTAT). Pada penelitian ini siswa telah memperoleh materi aturan pengisian tempat terlebih dahulu. Baru kemudian digunakan media yang nantinya akan digunakan untuk mengerjakan soal aturan pengisian tempat dengan soal yang berbeda. Dari penelitian ini diketahui bahwa hasil penelitian adalah peningkatan pemahaman siswa dalam mengerjakan soal aturan pengisian tempat menggunakan media Cognitive Tutor Authoring Tools (CTAT). Sehingga media Cognitive Tutor Authoring Tools (CTAT) dapat digunakan sebagai media pembelajaran alternatif untuk mengembangkan pemahaman siswa terhadap materi aturan pengisian tempat.